Fiscal policy, trigger points and interest rates: Additional evidence from the U.S. - Gerhard Reitschuler; Rupert Sendlhofer (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2011)
We empirically investigate whether the relationship between interest rates and public deficits/debt may be nonlinear for the U.S. Using threshold estimation, we find evidence of level-dependent effects on interest rates, implying a significant effect of projected deficits and debt in the U.S. only if the deficit surpasses approximately 5% of GDP.
Keywords: E43; E62; H62; 330; Public debt; public deficit; long-term interest rates; nonlinearity; threshold models; Domar model; Zins; Haushaltsdefizit; Nichtlineares Verfahren; Schätzung; USA